Analisis Peran Financial Technology Dalam Perkembangan Usaha Mikro Kecil Menengah (UMKM) di Indonesia - Rafika Putri (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
ABSTRACT This research aims to evaluate the role of Financial Technology (Fintech) in empowering Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The research method used is a literature review with a descriptive qualitative approach. The research results show that Fintech has made a positive contribution in supporting the growth of MSMEs through capital loan services, digital payments and financial regulation. However, the use of Fintech among MSMEs is still low, influenced by a lack of understanding and trust. MSME financial literacy can be improved through education and mentoring. As an opportunity, Fintech can expand access to financing, increase financial inclusion, and advance financial literacy. Challenges involve infrastructure, regulations and financial literacy that need to be addressed. In conclusion, Fintech has great potential to empower MSMEs, with cooperation between the government, financial institutions and Fintech industry players needed to create a conducive environment and protect MSMEs from illegal practices.